2018
DOI: 10.1111/jfs.12449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactoperoxidase system‐alginate coating on chemical, microbial, and sensory properties of chicken breast fillets during cold storage

Abstract: The main aim of this study was to investigate the effect of alginate coating samples without lactoperoxidase system (A-L 0) and alginate coating samples containing lactoperoxidase system (LPOS) at levels of 2% (A-L 2), 4% (A-L 4), and 6% (A-L 6) on the shelf-life of chicken breast fillets. Chemical tests, including total volatile basic nitrogen (TVB-N), peroxide value (PV), pH, thiobarbituric acid reactive substances (TBARS), and free fatty acids (FFA), bacteriological tests of aerobic mesophilic bacteria (AMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 40 publications
6
20
0
Order By: Relevance
“…Our observation was in agreement with Yousefi et al. () reported that the effects of LPOS‐alginate coating can prevent the formation of TVB‐N in chicken breast fillets during cold storage. Similar results were reported by Shokri, Ehsani, and Jasour (), as well.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our observation was in agreement with Yousefi et al. () reported that the effects of LPOS‐alginate coating can prevent the formation of TVB‐N in chicken breast fillets during cold storage. Similar results were reported by Shokri, Ehsani, and Jasour (), as well.…”
Section: Resultssupporting
confidence: 93%
“…So at the end of holding period, the number of aerobic mesophilic bacteria was less than 7 log cfu/g which is less than the number of bacteria that can be considered as an indicator of seafood spoilage (Gram & Huss, ). As well as our findings, similar results were reported about incorporated efficacy of LPOS and edible coating solution against mesophilic aerobic bacterial growth in chicken and fish (Jasour, Ehsani, Mehryar, & Naghibi, ; Molayi, Ehsani, & Yousefi, ; Shokri, Ehsani, & Jasour, ; Yousefi, Farshidi, & Ehsani, ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…who investigated the effect of the alginate–LPOS coatings on bacterial growth in chicken breast fillets. That study demonstrated that the higher level of LPOS has more controlling impact on Enterobacteriaceae with the passage of days (Yousefi, Farshidi, & Ehsani, ).…”
Section: Resultsmentioning
confidence: 94%
“…who observed that chicken breast fillets containing alginate coating incorporated with 6% LPOS has significant lower AMB counts compared with control samples without LPOS on days 8, 12, and 16. Also, they did not see any differences between samples until the fourth day of storage in refrigerator (Yousefi, Farshidi, et al., ).…”
Section: Resultsmentioning
confidence: 98%